2022
DOI: 10.1021/acs.jmedchem.2c00717
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of the First Family of Photo-Activatable Ligands for Melatonin Receptors

Abstract: Melatonin is a neurohormone released in a circadian manner with peak levels at night. Melatonin mediates its effects mainly through G protein-coupled MT 1 and MT 2 receptors. Drugs acting on melatonin receptors are indicated for circadian rhythm- and sleep-related disorders. Tools to study the activation of these receptors with high temporal resolution are lacking. Here, we synthesized a family of light-activatable caged compounds by attaching o … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The deprotection was originally performed with TFA in CH 2 Cl 2 , but significant acetal epimerization and incomplete conversion were observed. A screen quickly revealed that HBr in AcOH was a better alternative, , having both improved product formation and less acetal epimerization across several solvents. The product precipitates under these conditions, with CH 3 CN affording the best diastereoselectivity ratio (dr) and stability over time, likely due to low product solubility in this solvent (0.2 mg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…The deprotection was originally performed with TFA in CH 2 Cl 2 , but significant acetal epimerization and incomplete conversion were observed. A screen quickly revealed that HBr in AcOH was a better alternative, , having both improved product formation and less acetal epimerization across several solvents. The product precipitates under these conditions, with CH 3 CN affording the best diastereoselectivity ratio (dr) and stability over time, likely due to low product solubility in this solvent (0.2 mg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…Acetic acid imparted very little deprotection (entry 3). With 32 w/w% HBr in AcOH across several solvents, , the product was formed quickly with improved diastereoselectivity and precipitated (entries 4–7). We believe epimerization occurs primarily in the solution phase, and thus, precipitation limits ( S )-acetal formation.…”
Section: Resultsmentioning
confidence: 99%
“…Labeled subtype-specific ligands are highly desirable to determine the specific receptor present in cells and tissues naturally expressing the receptor(s). Outside of the strict domain of labelled compounds, recent studies reported the development of fluorescent ligands at melatonin receptors [80] as well as the synthesis of light-activatable caged melatonin compounds [81]. These molecules represent key elements in the toolbox for the pharmacological studies of melatonin receptors.…”
Section: Labeled Tracers For Melatonin Receptormentioning
confidence: 99%